The cost of radiology procedures using Activity Based Costing (ABC) for development of cost weights in implementation of casemix system in Malaysia - Ibrahim Roszita,; Amrizal Muhd Nur,; S. A. Zafirah,; Syed Mohamed Al Junid, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Presently there is a gross lack of information on cost and cost weights in many developing countries that implement casemix system. Furthermore, studies that employed Activity Based Costing method (ABC) to estimate the costs of radiology procedures were rarely done in developing countries, including Malaysia. The main objective of this study is to determine the costs of radiology procedures for each group in casemix system, in order to develop cost weights to be used in the implementation of the casemix system. An economic evaluation study was conducted in all units in the Department of Radiology in the first teaching hospital using the casemix system in Malaysia. From the 25,754 cases, 16,173 (62.8%) of them were from medical discipline. Low One Third and High One Third (L3H3) method was employed to trim the outlier cases. Output from the trimming, 15,387 cases were included in the study. The results revealed that the total inpatients’ charges of all the radiology procedures was RM1,820,533.00 while the cost imputed using ABC method was RM2,970,505.54. The biggest cost component were human resources in Radiology Unit (Mobile) (57.5%), consumables (78.5%) of Endovascular Interventional Radiology (EIR) Unit, equipment (81.4%) of Magnetic Resonance Imaging (MRI) Unit, reagents (68.1%) of Medical Nuclear Unit. The one highest radiology cost weight, was for Malaysia Diagnosis Related Group (MY-DRG®) B-4-11-II (Hepatobiliary and Pancreas Neoplasms with severity level II, 2.8301). The method of calculation of the cost of procedures need to be revised by the hospital as findings from this study showed that the cost imposed to patient is lower than the actual cost.